Real effective exchange rates for 178 countries: A new database - Zsolt Darvas (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2012)
We use data on exchange rates and consumer price indices and the weighting matrix derived by Bayoumi, Lee and Jaewoo (2006) to calculate consumer price index-based REER. The main novelties of our database are that (1) it includes data for 178 countries -many more than in any other publicly available database- plus an external REER for the euro area, using a consistent methodology; (2) it includes up-to-date REER values, such as data for January 2012; and (3) it is relatively easy to calculate REER against any arbitrary group of countries. The annual database is complete for 172 countries and the euro area for 1992-2011 and data is available for six other countries for a shorter period. For several countries annual data is available for earlier years as well, eg data is available for 67 countries from 1960. The monthly database is complete for 138 countries for January 1995-January 2012, and data is also available for 15 other countries for a shorter period. The indicators calculated by us are freely downloadable from the website of this working paper and will be irregularly updated.
Keywords: F31; 330; effective exchange rates; Kaufkraftparität; Datenbank; Indexberechnung; Welt